A history of research into ancient Egyptian culture conducted in southeast Europe - Tomorad, Mladen; Tomorad, Mladen (Archaeopress Egyptology, 2014)
The history of Ancient Egypt has been studied in the region of Southeast Europe since the end of the 19th century. In some of the countries this was not the case for various reasons, but mainly because of the undeveloped scholarly capabilities and institutions, insufficient funds for archaeological research in Egypt, and the lack of cooperation with scholars from other countries. From the 1960s, however, this situation has changed for the better. This book comprises a selection of papers in which scholars from various institutions of the region reviewed the different aspects of past studies and the development of the research of the Ancient Egypt in some countries, along with recent research in the field